Strategi Mahasiswa Muslim Teknik Dalam Menghadapi Kerusakan Moral di Era Digital - Pratama, Zikri Sandria; Abhinaya, R. Ahmad Faiz; Ramadhan, Gilang; Faqihuddin, Achmad (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The rapid development of digital technology has generated both opportunities and serious challenges for university students, particularly concerning moral degradation resulting from inadequate ethical awareness in the use of digital media. Muslim students in the Electrical Engineering Education Program at the Universitas Pendidikan Indonesia (UPI), Class of 2024, represent a group that is especially vulnerable to digital moral dilemmas due to their intensive engagement with technology for academic and social activities. This study aims to identify the forms of moral challenges encountered by students, analyze strategies for applying Islamic values in digital technology use, and formulate a model for strengthening digital character based on Islamic ethical principles for engineering students. This research employed a descriptive quantitative approach through a survey using a questionnaire containing 20 statements measuring five key dimensions: awareness of digital moral degradation, integration of Islamic values in technology use, positive digital behavior and self-control, religious engagement through digital platforms, and implementation of Islamic digital ethics. The study involved 32 students selected through purposive sampling. The findings reveal that students exhibit a high level of moral awareness, indicated by their recognition of moral degradation in digital spaces and understanding of its negative impacts. The integration of Islamic values also falls into a high category, reflected in students’ ability to reject negative digital content and their efforts to apply Islamic principles in technological activities. However, the practical implementation of Islamic digital ethics remains inconsistent, particularly in students’ willingness to correct peers who misuse technology and in maintaining consistent exemplary digital conduct. These findings highlight a gap between strong moral awareness and actual ethical behavior. Therefore, a comprehensive character-building strategy is needed, involving Islamic-based digital ethics training, supportive campus policies, and role modeling by lecturers and the academic environment to help students consistently apply Islamic values in their digital activities.